The Guns of Navarone - MacLean, Alistair, 1922-1987 (London Collins, 1966)
On the eastern Mediterranean island of Kheros, twelve hundred British men are garrisoned. In order to evacute these men before the inevitable German attach the "guns" have to be silenced. After landing by boat where the Germans least expect them, at the foot of the towering cliffs, beneath the impregnaable walls of rock, the five men must climb the cliffs.
Keywords: World War (1939-1945) -- Military campaigns -- Turkey